Graphic Design as Communication. - Barnard, Malcolm (Taylor and Francis, 2013)
What is the point of graphic design? Is it advertising or is it art? What purpose does it serve in our society and culture? Malcolm Barnard explores how meaning and identity are at the core of every graphic design project and argues that the role and function of graphic design is, and always has been, communication. Drawing on a range of theoretical approaches including those of Derrida, Saussure, Foucault, and Barthes, and taking examples from advertising, magazines, illustration, website design, comics, greetings cards and packaging, Graphic Design as Communication looks at how g.